Collective Narcissism and In-Group Satisfaction Are Associated With Different Emotional Profiles and Psychological Wellbeing - Golec de Zavala, Agnieszka (Frontiers in Psychology, 2019)
The social identity approach to wellbeing posits that social identifications provide psychological resources that contribute to individual wellbeing. Unless individuals identify with stigmatized groups or groups whose norms prescribe damaging behaviors, identifying with groups seems beneficial. This article explores the possibility that the different ways individuals approach the same social identity (labeled collective narcissism vs. in-group satisfaction) may be differentially associated with wellbeing. Results of four studies indicate that collective narcissism (a belief that the in-group’s exceptionality is not sufficiently appreciated by others) vs. in-group satisfaction, (a belief that the in-group is of a high value), although positively correlated, are associated with different emotional profiles. In Study 1a (N = 570, in Poland) and Study 1b (N = 778, in the U.S.), collective narcissism was uniquely positively associated with negative emotionality, whereas in-group satisfaction was positively associated with positive emotionality and negatively associated with negative emotionality. In Study 2 (N = 569, in Poland), collective narcissism and in-group satisfaction had opposite unique links with social connectedness, gratitude and self-criticism. In Study 3 (N = 393, in Poland), collective narcissism, but not in-group satisfaction, was associated with sensory processing sensitivity, genetically determined hypersensitivity to negative stimuli. Collective narcissism was associated with life satisfaction only via its link to in-group satisfaction. Together these results suggest that dispositional negative emotionality may incline individuals towards collective narcissism. The positive overlap with in-group satisfaction may link collective narcissist to the benefits of social identification and wellbeing.